Impact of Digital Health Interventions on Access, Quality, and Outcomes of Antenatal and Postpartum Care: A Systematic Review - Siska Ilannur Lubis; Desmawati Desmawati (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
Digital health technologies are increasingly adopted to enhance access, quality, and outcomes of antenatal and postpartum care, particularly in low- and middle-income countries (LMICs), yet empirical evidence on their effectiveness and implementation challenges remains heterogeneous. This systematic review aimed to evaluate the impact of digital health interventions on service utilization, quality of care, and clinical outcomes across the antenatal and postpartum continuum, while identifying multilevel implementation challenges. A systematic search of PubMed, Scopus, and Taylor & Francis (2021–2025) identified 19 eligible studies assessing digital health applications, including e-registries, clinical decision support systems (CDSS), telehealth, SMS/audio messaging, and community-based mHealth tools. Data were synthesized narratively across three domains: access and utilization, quality and user experience, and maternal–neonatal outcomes. The findings show that digital interventions consistently improved ANC attendance, timeliness, screening completeness, adherence to clinical guidelines, and communication quality between clients and providers. However, improvements in hard outcomes such as maternal or neonatal morbidity and mortality remained modest or non-significant. Key challenges were identified at multiple levels, including gender norms and device control at the household level; workload and infrastructure gaps at the facility level; data fragmentation and financing sustainability at the system level; and the need for co-design and behavior-theory-based development at the intervention level. Overall, digital health functions as an enabler that strengthens access and quality of antenatal and postpartum care, but measurable reductions in maternal–neonatal complications require integration with system strengthening, improved service coverage, and broader socio-cultural interventions.